Personal and Social Responsibility Development in a Volleyball Hybrid Positive Youth Development Program: A Mixed Methods Approach - Muñoz-Llerena, Antonio; Hernández-Hernández, Elena; García-de-Alcaraz, Antonio; Caballero-Blanco, Pablo (Frontiers in Psychology, 2021)
Positive Youth Development (PYD) programs are being used to foster holistic growth in children and adolescents. The hybridized application of two or more programs of this type has acquired special relevance in recent years. Although their application is common in the school context, there are few research studies that attempt their implementation in an extracurricular context. This study analyzed the effects of an intervention based on a hybrid PYD program on personal responsibility (PR) and social responsibility (SR) in youth volleyball players in an extracurricular context. A hybrid program was applied during the competitive season, with a total of 37 sessions with 30 girl students (15 experimental and 15 control) aged between 8 and 10 years (M = 8.87, SD = 0.82). A convergent mixed methods design was applied to integrate the following: (a) semi-structured interviews and field notes and (b) personal and social responsibility questionnaires. The results indicated that the implementation of the hybrid program appeared to yield a positive perception of learning in both the participants and the coach. Although there were no statistically significant intergroup or intragroup differences, the findings suggest that the hybrid program seems to be effective in fostering PR and SR in youth girl volleyball players.